Effects of Four-Week Kayak Training on Three-Dimensional Paddling Kinetics, Body Kinematics, and Electromyography Activity in a Novice Paddler: A Case Study - Kinugasa, Ryuta; Kubo, Shimpei; Endo, Keiko (Frontiers in Sports and Active Living, 2021)
From a biomechanical viewpoint, no longitudinal quantitative studies have been conducted on inexperienced paddlers. The present study aimed to investigate changes in three-dimensional paddling kinetics and kinematics, whole-body kinematics, and muscle activity with four-week on-water kayak training in a novice paddler. The participant practiced kayak paddling on river for four weeks. Before and after training, paddling kinetics and kinematics, body kinematics, and electromyography (EMG) activity were measured using a kayak ergometer. After the four-week training, the time required for on-water paddling for 270 m was reduced by 7.3% from pre to post training, while the average impulse in the x-direction significantly (P < 0.001, partial eta squared [η2] = 0.82) increased from 71.9 ± 1.9 to 91.1 ± 5.4 N kg−1 s−1. Furthermore, with training, the stroke rate and stroke length in the x-direction significantly (P < 0.001, partial η2 = 0.80 and 0.79, respectively) increased from 62.8 ± 1.2 to 81.0 ± 2.9 spm and from 1.53 ± 0.04 to 1.71 ± 0.02 m, respectively. After training, the transition time significantly (P < 0.001, partial η2 = 0.32) decreased (from 0.04 ± 0.01 to 0.01 ± 0.01 s), and there was an increase in paddle catch position (from −0.88 ± 0.01 to −1.04 ± 0.03 m). The pull time was not significantly changed (P = 0.077, partial η2 = 0.08) because of the increasing stroke length after training, meaning that substantial pull time, which defined as pull time relative to the stroke displacement, was shorter in post-training than in pre-training. The relative change in average impulse in the x-direction with training was significantly (r = 0.857, P = 0.014) correlated with that of vastus lateralis EMG. These results indicated that after four-week kayak training of the novice paddler, the key mechanism underlying time reduction to perform on-water paddling for 270 m was associated with (1) increased average impulse along the propulsive direction caused by an increase in vastus lateralis EMG and (2) a higher stroke rate, which was attributed to a reduction in the pull and transition times.